Jezioro Dąbie polem refulacyjnym? = Lake Dąbie as silt up field? - Borkowski, Marek; Mrozińska, Gabryela; Szutowicz, Julita (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The fields for the polluted material from docks dredging are planned on Dąbie Lake. They can really be a threat for present natural, touristic and recreational values of the lake.
Keywords: 3 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: zrównoważona gospodarka zasobami naturalnymi" (24-25.06.2004)